The prevalence of obstructive sleep apnea in Greek young adults in primary care - Kleisiaris, Christos; Maniou, Maria; Papathanasiou, Ioanna; Tsipoliti, Georgia; Spitalioraki, Eirini; Sarafis, Pavlos (My University, 2014)
The syndrome of obstructive sleep apnea (OSA) has for three decades about an identifiable and recognized pathological entity with multiple consequences in the public health.The appearance of the OSA is estimated 2-4% of the world population while some of the diseases associated with such obesity and cardiovascular diseases are growing faster even by the younger age. The aim of the present study was to identify the prevalence of obstructive sleep apnea syndrome (OSA) in a sample of students of Technological Educational Institute of Crete.Material and Method: The sample consisted of 400 students. Obstructive sleep apnea was quantified using the Berlin questionnaire which apart from the demographic data, it included three categories (10 questions) designed to illicit information regarding snoring (category 1), daytime somnolence (category 2) and the presence of obesity and/or hypertension(category 3). Somatometric measurements (Height, Weight, hip and waist circumference) and arterial blood pressure were carried out. Also, apprised parameters that concern the heredity the habit of smoking, nasal congestion, sudden awakenings and respiratory problems. BMI was calculated as the body weight divided by the square of height (expressed in kg/m2). Analysis included Kruskal Wallis test, the Mann Whitney test analysis, the non-parametric Mann Whitney test analysis, the Spearman correlation coefficient and the Coefficients of Cronbach's. The data analysis was performed using the statistical programme IBM SPSS 19.0.Results: The prevalence of OSA was found 1.0% of the sample. Only 4 students were diagnosed with high risk and 48 (12.0%) students with low risk according to Berlin Questionnaire. Snoring had the highest frequency 8% and followed by obesity with 5.3%. Also, snoring have all the people with increased risk for OSA in contrast to those with low or no risk (100% vs. 33.3% and 3.4% respectively, p = 0,008). Significantly more women were at high risk than men (1.5% vs. 0.5%, p = 0,040) but fewer low (8.1% vs 15,8%, p = 0,040). In addition, older students had significantly higher prevalence of low and high risk (p-trend = 0,005) while those with a high or low risk had significantly higher average levels of obesity indices, p <0,001. Smoking, nasal congestion and heredity do not associated with the risk for OSA as opposed to sudden awakenings, p = 0,005 and respiratory problems, p <0,001. Conclusions: Although the very low frequency of OSA, snoring, obesity, the age and the gender consists strong predictors of OSA.
Keywords: Snoring; Obesity; Obstructive sleep apnea